(3JYdje GdQjGVjGJ dPhj UYhHGJ GdJYde (B:s (3Odjd Yedj dQjGV GdCWaGd (B/s - (3TYHGf, TYHGf Mafjs; (3GdefjQ, QGfOG YHO GdYdjes ((3YeGf (B- (3GdeedcI GdCOQfjI GdgGTejI (B:s (3eQcR OjHhfh dJYdje GdJacjQ ,s, 2012)
(3jeKd GdcJGH CMO GdCOdI GdYedjI GdEQTGOjI deYdeGJ QjGV GdCWaGd, hChdjGA CehQ GdCWaGd, ajeG jJYdb HGcJTGa, hJYdje hJYde EMOi GdaFGJ GdNGUI, hgj aFI Phi UYhHGJ JYde GdQjGVjGJ (B/ (3Phj bUhQ GdegGQGJ GdQjGVjI bHd GdCcGOjejI ; MjK jMGhd GdELGHI Yf GdJSGDdGJ, hefGbTI GdbVGjG GdTGFcI GdeJYdbI HgPg GdaFI ef GdCWaGd, eY eMGhdI ERGdI GdJOGNd Hjf GdYOjO ef GdeUWdMGJ, hGdPj jJQJH Ydjg GdbjGe HeeGQSGJ ZjQ edGFeI, hjbOe GdcJGH NWhWG EQTGOjI dcjajI GcJTGa Jdc GdaFI HWQb ehVhYjI, hGdeeGQSGJ GdedGFeI aj OYe GdJYde GdQjGVj dgPg GdaFI ef NdGd efgL GdQhVI(B.s
(3HHdjhLQGajI (B: (3UaMI (B345-354.s
Keywords: (3JYdje NGUs -- (3QjGVjGJs -- (3OQGSI hJYdje (B((3WahdI eHcQI(B)s -- (3GdCWaGd HWjFhG GdJYdes